Peradaban Islam : Masa Kebangkitan Kembali - Mardinal Tarigan; M. Fadly Indrawan; Nora Khairani; Nur Sakinah; Windi Amelia Harahap (Journal on Education, 2023)
In the 18th century, the Islamic world plunged into the abyss of its deepest collapse. There is no longer the productivity of Muslims in the fields of politics, economics, science, art, and so on like 14 centuries of its heyday ago. Muslim criticism of Western modernization (modernism) is growing rapidly in various forms, both in the form of intellectual movements and socio-political movements. This diversity makes it difficult to find appropriate terms that cover all of these symptoms. The term used by the West as the first ball rolling ball of Islamic revival, among others, is revivalism (the notion of getting a revival), activism (political teachings that advocate violent action to achieve political goals), billionarism, Islamic militancy (activities that emanate from the height of fighting spirit, valor courage among Muslims), messianism, resurgence (reappearance, revival with more numbers than before), and reassertion (re-enforcement).